Evaluation of texture in Serra da Estrela cheese manufactured in different dairies - Guiné, Raquel (2019)
Serra da Estrela cheese is a traditional product from artisanal manufacture using raw ewe’s milk coag- ulated with dried, wild thistle flower. The present study aimed to investigate the variation of textural properties in Serra da Estrela cheeses manufactured in different dairies through time, namely from April to June, following the end of the cheese making season. Three types of tests were conducted: compression, puncture and spreadability. These were carried out on samples coming from six differ- ent dairies situated in the PDO (Protected Designation of Origin) region of this type of cheese.The results obtained showed some non-negligible differ- ences for some textural properties between the top and bottom sides of the cheeses evaluated, as well as between cheeses from different dairies. Nevertheless, the proper- ties of springiness, resilience, cohesiveness and adhesive- ness (all from the compression test), were not significantly different in the samples analysed. In what concerns the variations along the milking season, it was possible to conclude that three of the considered dairies produced cheeses with a more constant textural profile in the period comprised between April and June. Furthermore, statis- tical analysis revealed that the correlations between the textural properties were strong for some interactions between properties form the same test and/or from similar nature.